Understanding heritage in Singapore : the irony behind Chinatown, Little India and Kampong Glam - Kam, Natalie Jie Yi (2018)
In the landscape of Singapore today, built heritage is often ignored considering how the country is the epitome of a ‘concrete jungle.’ As such, spaces that contain rich culture and history are often times taken for granted in the pursuit of economic progress and higher standards of living. Such is the case when it comes to the spaces of Chinatown, Little India and Kampong Glam. Existing once as ethnic settlements, they have been transformed in the 1980s into historic districts that were deemed as important in the eyes of the Singapore government. This essay is concerned with the transformation of these spaces from settlements to forms of built heritage, examining the irony behind the government’s intentions with regards to conservation. From this, the essay will aim to reveal the economic intentions masked behind nation-building reasons of conservation efforts, further putting into question the concept of ‘heritage’ today.